Cultural competence-based framework: a multilevel and multidimensional perspective on contemporary science culture - Minh, Thai Thi; Osei-Amponsah, Charity (SAGE Publications, 2024)
This article presents a cultural competence-based (CCB) framework to analyse contemporary science culture. Starting from the observation that two separate views of culture-as-context and culture-as-practice cannot address the ongoing transitions in the contemporary sciences towards esoteric–exoteric trans-sphere governance and multicultural science, we introduce key ideas from ‘older’ varieties of competence-based culture theories. We argue that a spectrum of cultural and sociocultural systems shapes contemporary science culture by being (un)supportive of individual scientists acquiring cultural competence and guiding scientists’ research practices. In contrast, individual scientists’ cultural competence shapes the fabrication of cultural and sociocultural systems through their scientific practices, thereby shaping contemporary science cultures. We also synthesize different concepts of science culture, reflect the transitions in contemporary sciences and construct three dimensions of the cultural system, sociocultural system and cultural competence from various elements. By providing a conceptual framework that contributes to a better understanding and management of contemporary science culture, we hope to enhance effective work ethics and fit-for-purpose science knowledge to address emerging ‘wicked’ societal challenges.